The Role of The Inter-Village Cooperation Office In Protecting, Managing, Preserving The Results of The National Community Empowerment Program of Banyuasin District - Sari, Dian Novita Fajar (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this study is to identify all integrated protection, management and security measures to spread the results of legal certainty, support and partnership development carried out by SPP (Women's Savings and Credit) of PNPM and BKAD. The problem is that the SPP groups in Banyuasin still have different opinions. This study seeks to answer this question by identifying the role of BKAD in maintaining, managing and sustaining the results of SPP implementation in Banyuasin. A rational method was chosen to analyze the research questions. Informants were identified through purposive sampling and snowball methods. As a result, three research questions were identified. First, BKAD provides the necessary guarantees for the release of PPS funds and resources through negotiation. Second, BKAD coordinates all parties of the PPS and implements administrative actions restructuring consumer loans. Third, environmental initiatives led by BKAD promote sustainable plant protection.